2018
DOI: 10.1182/blood-2018-03-841171
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 trial of vadastuximab talirine combined with hypomethylating agents in patients with CD33-positive AML

Abstract: Treatment of acute myeloid leukemia (AML) among the elderly is challenging because of intolerance of intensive therapy and therapy-resistant biology. Hypomethylating agents (HMAs) are commonly used, with suboptimal outcomes. Vadastuximab talirine is a CD33-directed antibody conjugated to pyrrolobenzodiazepine (PBD) dimers. Preclinically, HMAs followed by vadastuximab talirine produced upregulated CD33 expression, increased DNA incorporation by PBD, and enhanced cytotoxicity. A combination cohort in a phase 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 33 publications
(37 reference statements)
0
42
0
1
Order By: Relevance
“…This was the case with SGN-CD33A, a monoclonal antibody directed towards CD33 conjugated with a DNA-crosslinking pyrrolobenzodiazepine dimer. 55 A phase I trial found that the combination of CD33A with azacitidine yielded responses in 70% of patients with the majority of them achieving Minimal residual Disease (MRD) negativity, 56 but the phase III CASCADE trial comparing vadastuximab and HMAs with HMAs alone was put on hold due to excessive toxicity. Similarly, volasertib, a small molecule inhibitor of Polo-like kinase I that induces cell cycle arrest and apoptosis, in combination with LDAC demonstrated enhanced overall response rates (31% versus 13.3%, respectively), prolonged EFS (5.6 months versus 2.3 months, respectively), and OS (8 months versus 5.2 months, respectively) compared with LDAC alone.…”
Section: How To Escape the Dilemma? The New Generation Of Low-intensimentioning
confidence: 99%
“…This was the case with SGN-CD33A, a monoclonal antibody directed towards CD33 conjugated with a DNA-crosslinking pyrrolobenzodiazepine dimer. 55 A phase I trial found that the combination of CD33A with azacitidine yielded responses in 70% of patients with the majority of them achieving Minimal residual Disease (MRD) negativity, 56 but the phase III CASCADE trial comparing vadastuximab and HMAs with HMAs alone was put on hold due to excessive toxicity. Similarly, volasertib, a small molecule inhibitor of Polo-like kinase I that induces cell cycle arrest and apoptosis, in combination with LDAC demonstrated enhanced overall response rates (31% versus 13.3%, respectively), prolonged EFS (5.6 months versus 2.3 months, respectively), and OS (8 months versus 5.2 months, respectively) compared with LDAC alone.…”
Section: How To Escape the Dilemma? The New Generation Of Low-intensimentioning
confidence: 99%
“…Vadastuximab talirine (SGN‐CD33A) is a CD33‐directed antibody conjugated to pyrrolobenzodiazepine (PBD) dimers. Addition of vadastuximab talirine to HMAs induced remission, but at the cost of increased myelosuppression and nonhematologic AEs like fatigue, nausea, and diarrhea . The phase III CASCADE trial evaluated vadastuximab talirine in combination with the HMAs vs HMA alone in older patients with newly diagnosed AML, but was terminated early due to increased deaths due to veno‐occlusive disease (VOD) (NCT02785900).…”
Section: Antibody Drug Conjugatesmentioning
confidence: 99%
“…CD44 is the receptor for hyaluronic acid, for which inhibition prevented engraftment of CML and AML cells in vivo (Jin et al, 2006). Similar pre-clinical studies have been performed targeting other cell surface molecules, including VCAM-1 (Jacamo et al, 2014) and CD33 (Fathi et al, 2018). Indeed, several groups have reasoned that targeting the microenvironment could help eradicate myeloid LSCs, which includes treatment with the CXCR4 antagonist, plerixafor (AMD3100), and strategies targeting the IL-3 receptor alpha chain, CD123 (Tables I, SI).…”
Section: Opportunities For Therapeutic Intervention and Future Directmentioning
confidence: 92%